Motivation and Mathematics Achievement: A Case Study of Grade 11 students in Ghana (Department of Mathematics, Universitas Negeri Semarang, 2022)
This study investigated the relationship between motivation and performance in mathematics using Deci and Ryan's Self Determination Theory. The participants were 2,575 grade 11 students from 10 senior high schools in the Cape Coast Metropolis, Ghana. The study employed a quantitative research approach and used a questionnaire and an achievement test to collect data. Descriptive and inferential statistics were used to analyze the data. The study found that only amotivation and introjection, among the five sub constructs of motivation considered in the study, recorded statistically significant contributions (p ˂ .05) to students’ achievement. Teachers, lecturers, and researchers may need to seek practical ways to promote intrinsic motivation in students for better engagement with mathematics. The study also indicated the likelihood of different kinds of amotivation with varied influences on the learning of mathematics. As a result, more investigation is required.